Formulasi Penempatan Sensor Suhu Pada Green House - Hermawan, Rudi; Adhy, Dewanto Rosian; Maesaroh, Siti; Anggara, Mohamad Bayu; Mauhib, Akpil; Rosada, Nyataku Ibnu; Suhendar, Asep; Noor, Yudin Wahyudin (Politeknik Harapan Bersama Tegal, 2024)
The application of Internet of Things (IoT) technology is currently increasingly widespread in various aspects of human life, both in agriculture, animal husbandry, education, and in various industries or other institutions. However, the problem that is often encountered is that the application of IoT technology is only limited to function without considering the effectiveness and efficiency of the sensors used in the technology. This also applies to the IoT-based system in the Greenhouse, one of the products developed by the Informatics Engineering Study Program, Mayasari Bakti University. Temperature plays an important role in the process of cultivating plants in a greenhouse, so the sensor must be calibrated accurately according to the size of the greenhouse. Often, the temperature sensor used in the greenhouse cannot reach the entire area so that anomalies occur in temperature monitoring which will ultimately affect the quality of the harvest.In this study, the temperature sensor is the main focus in the development of a large-scale greenhouse control system. This study uses an experimental research method that focuses on determining the causal relationship between the main object and related factors. The study was conducted in a greenhouse with an area of 5 x 6 meters. The results showed that the DHT22 sensor was more effective than the LM35 and DHT11 sensors. For comprehensive temperature monitoring in this greenhouse, 12 DHT22 sensors are required arranged in 4 rows and 3 columns for optimal coverage.